Innovative ceramic-matrix composite substrates with tunable electrical conductivity for high-power applications. Issue 1 (31st December 2022) - Kenfaui, Driss; Valdez-Nava, Zarel; Laudebat, Lionel; Locatelli, Marie-Laure; Combettes, Céline; Bley, Vincent; Dinculescu, Sorin; Tenailleau, Christophe; Dufour, Pascal; Guillemet-Fritsch, Sophie
ABSTRACT: A wide band gap semiconductor power module can operate at higher voltages as compared with its traditional silicon counterpart. However, its insulating system undergoes stronger electric fields at the triple point between the ceramic substrate, the metallic tracks and the encapsulating polymer, which can dramatically reduce its lifespan. Here we report an original concept based on the local modification of the substrate properties to mitigate such electrical stress. Numerical simulations revealed its potential to reduce this constraint by up to 50%. This concept was realized by developing, through a practical approach, a novel substrate made of an AlN-based ceramic (material A) integrating a nanocomposite volume endowed with controlled properties and geometry. This approach implies first the spark plasma sintering of the AlN powder with additives (Y2 O3, CaF2 ) to endow the material A with a very low electrical conductivity (σ) and high thermal conductivity (k). Graphene nanoplatelets (GNP) were incorporated within this material to fabricate a nanocomposite with a controlled σ anisotropy that otherwise reached a striking ratio of 10 6 at 20°C for 1.25 vol% GNP. Our approach secondly aimed at developing an effective process allowing to integrate this nanocomposite into the material A with a very high degree of reproducibility. It finally consisted in establishing the electrical contacts on the achieved substrate and encapsulating it for breakdown testing. The novel substrate enabled a mitigation of the electrical constraint by diminishing its intensity and shifting it from the triple point to a less constrained area. It already brought an improvement in breakdown voltage (VB ) by 15% as compared to the traditional substrate, and revealed the potential for achieving higher VB as well. This work lays the foundation for the development of novel multifunctional ceramic-matrix composite substrates sought for power electronics as well as for other potential applications. GRAPHICAL ABSTRACT: uf0001